2007
DOI: 10.1002/ajh.20926
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α inhibitor etanercept and hematologic malignancies: Report of a case and review of the literature

Abstract: We report here a 57-year-old man treated with etanercept for 6 months for psoriasis who developed myelodysplasia with acute myeloid leukemia. Leukemia cells had distinct karyotype associated with poor prognosis. The patient did not respond to cytosine arabinoside 100 mg/m 2 continuous infusion over 7 days with daunorubicin 45 mg/m 2 daily for 3 days. He also did not respond to salvage induction therapy with gemtuzumab (6 mg/m 2 on day 1 and 4 mg/m 2 on day 8) and intravenous continuous infusion cytosine arabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…7 In the literature, acute leukemia cases due to anti-TNF-a treatment were also reported; however, not as much as lymphoma. [8][9][10][11][12][13][14][15][16] First case was published in 2003. 8 The Food and Drug Administration declared 44 AML cases which developed under the treatment of anti-TNF-a drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In the literature, acute leukemia cases due to anti-TNF-a treatment were also reported; however, not as much as lymphoma. [8][9][10][11][12][13][14][15][16] First case was published in 2003. 8 The Food and Drug Administration declared 44 AML cases which developed under the treatment of anti-TNF-a drugs.…”
Section: Discussionmentioning
confidence: 99%
“…9 The relevant case reports about acute leukemia after anti-TNF-a treatment published on MEDLINE are reviewed in Table 1. [10][11][12][13][14][15][16] Ten of the 13 reported patients who developed acute leukemia after anti-TNF-a had AML. AML development may be attributed to higher incidence of this disorder in adults; however, Ph chromosome positivity in all of the three ALL cases is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al reported one case of hematologic malignancy (acute myeloid leukemia associated to myelodysplasia) after 6 months from Etanercept therapy for psoriasis [127]. Moreover, a previous case report of acute myeloid leukemia has been described by Bakland et al [128].…”
Section: Tnf-a Inhibitors and Cancermentioning
confidence: 98%
“…Also blood tests should be done prior to begin biological therapy to detect factors related to premalignancies to avoid increasing risk of malignancies [127]. Anderson et al proposed that patients with highly active disease and/or chronic exposure to immunosuppressant therapies may enhance lymphoma development and suggest fulfilling malignancies history to prevent carcinogenesis [17].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Because TNF has a tumor-reducing capacity, treatment with anti-TNFs might theoretically promote the formation of tumors [40,41] We found several reports that focused on the risk of lymphoma in patients with RA who were treated with anti-TNF agents.…”
Section: Malignanciesmentioning
confidence: 99%